2002
DOI: 10.1038/sj.bjc.6600173
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear distribution of porphobilinogen deaminase (PBGD) in glioma cells: a regulatory role in cancer transformation?

Abstract: Recently, considerable interest has been directed to red-fluorescence photodiagnosis of brain and other tumours during surgery using the protoporphyrin IX natural precursor, 5-aminolaevulinic acid. In the present study we focused on the role of the rate-limiting enzyme porphobilinogen deaminase in glioma C6 cell activity, differentiation and sub-cellular distribution. Over-expression of the human housekeeping porphobilinogen deaminase in the glioma cells, using the housekeepingporphobilinogen deaminase plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…We have already shown that the major fraction of PBGD in C6 glioma cells was found in the nucleus (Greenbaum et al, 2002). Figure 6 reveals the subcellular localisation of PBGD in B16 melanoma cells.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…We have already shown that the major fraction of PBGD in C6 glioma cells was found in the nucleus (Greenbaum et al, 2002). Figure 6 reveals the subcellular localisation of PBGD in B16 melanoma cells.…”
Section: Resultsmentioning
confidence: 74%
“…All the coding regions of the fragments were amplified from pHK-PBGD (pLY-81) (Greenbaum et al, 2002) using different primers for each fragment. The PCR products were cut by the restriction enzymes BglII and EcoRI, and were ligated to pEGFP-N1 (Clontech, Palo Alto, CA, USA) in frame.…”
Section: Preparation Of Fragments Of Pbgd Fused To Gfpmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the PBGD, including the nuclear fraction, is downregulated during butyrate-induced cell differentiation of glioma (Greenbaum et al, 2002) and melanoma cells (not yet published), which points to a possible nuclear function of PBGD. Butyrate-dependent induction leads to histone hyperacetylation via inhibition of histone deacetylase (ADAC), inhibition of histone phosphorylation, and DNA methylation (Archer and Hodin, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that PBGD is imported into the nucleus of glioma C6 cells in addition to the fraction, that remains in the cytoplasm (Greenbaum et al, 2002). Nuclear import of many proteins was shown to be dependent on a specific import mechanism via RanGTPase and on the cytosolic or nuclear localization of this enzyme (Yoneda, 2000;Quimby and Corbett, 2001).…”
Section: Introductionmentioning
confidence: 99%